Re-aktualisasi Tato pada Iklan A Mild “You Will Figure It Out” dalam Membentuk Positioning Produk - Aisyi Syafikarani (Institut Seni Indonesia Yogyakarta, 2018)
Abstract.Indonesia has a variety of cultures that produce works of art and one of them is a tattoo. The oldest tattoos in Indonesia are those owned by the Mentawai and Dayak tribes. But in its development the meaning of tattoos has been re-actualized into bad value. The shift in interpretation of tattoo stigma is used by A Mild to shape the positioning of its products in the minds of consumers. A Mild